Resistance and Counter-Hegemonic Discourse in Laila Halaby’s West of the Jordan - Ouhiba, Nawel Meriem (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
Arab Americans have been subject to decades of racism, discrimination, negative stereotyping, and hostility in the United States. These problems have motivated Arab American cultural leaders and creative writers to put forward in their texts the challenges that they face in the United States. These problems have also encouraged Arab American writers to try to find their place and identity in the American community. Knowing that most of the key texts in contemporary Arab American literature are written by women as counter-narratives to the Western negative stereotypes and a reflection to the difficulties they face because of their feelings of gender discrimination and their sense of possessing hybrid identities or hyphenated identities. It should be noted that their writings are playing an important role in creating insurgent women who not only are deconstructing the several modalities of female identity for Arab women in the West, but also rejecting their homelands’ patriarchal, nationalist, and anti-colonial emancipatory discourses and resisting Western imperial hegemonies. The present paper examines how Laila Halaby in West of the Jordan is transgressing a normative paradigm already conceptualized in the mainstream Western culture for the Arab-American woman hybrid. Her characters are living a transformational experience that leads them to challenge hegemonic constructions of the dominant knowledge, resist the different contradictions and ambivalences of their native patriarchal cultures, and find a political voice to fight their invisibility and oppression.